Lebaran Inflation and Adaptation of MSMEs Economy: (Case Study in the Culinary Sector) - Hernaningsih, Fery (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
Lebaran is one of the annual moments that has a major impact on the economy, especially for the culinary MSME sector. The surge in demand is often accompanied by an increase in the price of raw materials which causes seasonal inflation. Seasonal inflation that occurs during the Lebaran period has a significant impact on the micro, small, and medium enterprises (MSMEs) sector, especially in the culinary sector. In the Jl. Antene IV Housing, Radio Dalam, South Jakarta, approaching the time to break the fast, many small business actors sell various foods and drinks for breaking the fast, such as takjil and special Ramadan dishes. Each trader determines the price according to the production costs and desired profits. Traders adapt to the increase in raw material prices by increasing selling prices and diversifying products. This study aims to analyze how culinary MSMEs adapt to fluctuations in raw material prices, increasing demand, and other operational challenges during the Lebaran period. Using a qualitative approach, this study examines the strategies implemented by culinary MSMEs in maintaining the stability of their businesses. Data were obtained through in-depth interviews with business actors and observations in several culinary centers that experienced a spike in demand during Lebaran. The results of the study show that the main strategies used include price adjustments, product diversification, and more efficient stock management. These findings are expected to provide insight for MSMEs in facing economic challenges during the Eid moment and become a consideration for the government in designing policies that support the sustainability of MSMEs.